The impact of external auditing in business valuation: a case for United Kingdom. - Carvalho, Tomás Costa de Paula (2019)
This research intends to measure and analyze the influence of external auditing on the UK companies’ valuation, which was modeled through a multiple linear regression that has as explanatory variables: Tenure, Fees, Scope and Materiality; and as dependent variables: Tobin’s Q and PB. Using the FTSE 100 as the reference market index and considering a linear relationship between business valuation and the variables indicated, this paper allows to infer about its effects. The hypothesis that these audit characteristics are not significant is rejected and each variable contributes for the value of the firms. Moreover, it also suggests that size has a relevant influence in the study and that some regression’s specifications are valuable insights for interpretation purposes